Quantitative and/or Qualitative Methods in the Scientific Study of Religion - Brink, T. L. (Zygon, 1995)
Abstract. Qualitative research methods are essential to provide richness, but they are vulnerable to distortion of data by theory. The quantitative approach is necessary for the precision of hypothesis testing, but, by itself, this method is too critical to be creative. Religious studies should use both methods in alternate phases, with the qualitative approach creating new hypotheses and the quantitative approach critically testing them.